1979
DOI: 10.1016/0304-3959(79)90125-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibrositic myofascial pain in intermittent claudication. Effect of anesthetic block of trigger points on exercise tolerance

Abstract: The blocking of trigger points in the calf by the local injection of an anesthetic agent was performed in 15 patients with intermittent claudication. Reactive and exercise hyperemia, work load and duration of exercise were recorded before and after infiltration of the trigger points. Reactive hyperemia does not change, but the exercise tolerance of the leg significantly improves after local blocking of the trigger areas and the exercise hyperemia increases because of the higher work load. The pain pattern of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Table 2 summarizes the details of the 14 trials that investigated direct wet needling. Wet needling with different substances was compared in 10 studies, 8 of which found that the Macdonald et al 22 Not predominantly myofascial pain Petri et al 23 Not predominantly myofascial pain Petri and Langley 24 Not predominantly myofascial pain Berry et al 25 Not predominantly myofascial pain Crockett et al 26 No needling intervention included Dacre et al 27 Not predominantly myofascial pain Dorigo et al 28 Not RCT Fischer 29 Not RCT Fox et al 30 Not predominantly myofascial pain Freund and Schwartz 31 Not RCT Frost et al 32 Same as trial in Frost et al 77 Gallacchi et al 33 Not predominantly myofascial pain Gnatz 34 Not RCT Gunn et al 35 Not predominantly myofascial pain Hay 36 Not RCT Hendler et al 37 Not RCT Heuser 38 Not randomized Hollingworth et al 39 Not predominantly myofascial pain Hong and Hsueh 40 Same intervention in each group Jacob 41 Not RCT Jaeger and…”
Section: Data Synthesismentioning
confidence: 99%
“…Table 2 summarizes the details of the 14 trials that investigated direct wet needling. Wet needling with different substances was compared in 10 studies, 8 of which found that the Macdonald et al 22 Not predominantly myofascial pain Petri et al 23 Not predominantly myofascial pain Petri and Langley 24 Not predominantly myofascial pain Berry et al 25 Not predominantly myofascial pain Crockett et al 26 No needling intervention included Dacre et al 27 Not predominantly myofascial pain Dorigo et al 28 Not RCT Fischer 29 Not RCT Fox et al 30 Not predominantly myofascial pain Freund and Schwartz 31 Not RCT Frost et al 32 Same as trial in Frost et al 77 Gallacchi et al 33 Not predominantly myofascial pain Gnatz 34 Not RCT Gunn et al 35 Not predominantly myofascial pain Hay 36 Not RCT Hendler et al 37 Not RCT Heuser 38 Not randomized Hollingworth et al 39 Not predominantly myofascial pain Hong and Hsueh 40 Same intervention in each group Jacob 41 Not RCT Jaeger and…”
Section: Data Synthesismentioning
confidence: 99%
“…225,226,229 Also supporting this modality’s capability of improving perfusion, is a study showing infiltration of TrPs reduces symptoms of intermittent claudication. 230 Symptomatically, a person constantly exerting effort against such forces of a suffocating fascia would likely feel chronic fatigue and soreness, while accumulating nociceptive substances in muscles in a chronically tonic body; and active loci induced “energy crises”. With regards to active loci, it is possible the cell has its own ways to oppose this abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…220 Also supporting this modality's capability of improving perfusion, is a study showing infiltration of TrPs reduces symptoms of intermittent claudication. 221 Symptomatically, a person constantly exerting effort against such forces of a suffocating fascia would likely feel chronic fatigue and soreness, whilst accumulating nociceptive substances in muscles in a chronically tonic body, and widespread "energy crises". A reader adopting this "biological ethos" should not be surprised, for example, by a study finding that fibromyalgia patients have elevated serum tau and amyloid beta levels, since studies suggest amyloid beta and the cytoskeletal protein tau and are affected by, or compensate for, mechanical stress.…”
Section: Bizarrely Wang Et Al Find a Bidirectional Association Between Fibromyalgia And Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 99%
See 2 more Smart Citations